2013
DOI: 10.1021/cb400660a
|View full text |Cite
|
Sign up to set email alerts
|

GSK3 Alpha and Beta Are New Functionally Relevant Targets of Tivantinib in Lung Cancer Cells

Abstract: Tivantinib has been described as a potent and highly selective inhibitor of the receptor tyrosine kinase c-MET and is currently in advanced clinical development for several cancers including non-small cell lung cancer (NSCLC). However, recent studies suggest that tivantinib’s anticancer properties are unrelated to c-MET inhibition. Consistently, in determining tivantinib’s activity profile in a broad panel of NSCLC cell lines, we found that, in contrast to several more potent c-MET inhibitors, tivantinib reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 27 publications
5
59
0
Order By: Relevance
“…Thus, SEMA3A was not considered for subsequent experiments. In contrast, GSK3β inhibition, FYN inhibition and MET inhibition have been shown as promising strategies for combating cancer [35-37]. In our study, both FYN inhibition and MET inhibition were synthetic lethal with p53 activation in A549 cells (Table S6).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Thus, SEMA3A was not considered for subsequent experiments. In contrast, GSK3β inhibition, FYN inhibition and MET inhibition have been shown as promising strategies for combating cancer [35-37]. In our study, both FYN inhibition and MET inhibition were synthetic lethal with p53 activation in A549 cells (Table S6).…”
Section: Resultsmentioning
confidence: 64%
“…In our study, both FYN inhibition and MET inhibition were synthetic lethal with p53 activation in A549 cells (Table S6). Although not synthetic lethal with p53 activation, according to the genomic screening data, GSK3β is well known to act upstream of FYN kinase [38], and GSK3β inhibition by either siRNA or chemical inhibitors has been shown to decrease MET activity levels in A549 cells [35]. Moreover, among GSK3β, FYN and MET, only GSK3β has been shown to bind p53 [39, 40] and to modulate p53-mediated apoptosis [41, 42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other various tumor entities, resistance against EGFR inhibition or resistance against anti-VEGF therapy has been demonstrated to be mediated by compensatory upregulation of phosphorylated c-Met as an alternative signaling pathway. Inhibition of c-Met has been discussed as a potential target in combination therapies in order to overcome a c-Met-induced escape from EGFR inhibition [50,51,52,53,54,55,56] or escape from anti-VEGF therapy [31,57,58,59,60], as has been demonstrated in various tumor entities. These mechanisms have also been discussed for neuroendocrine tumors [19,20,21,31,61].…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies, including ours indicated that GSK3 inhibition directly impairs the cancer cell function in vitro, and growth and metastasis of multiple cancers in vivo such as prostate [13], pancreas [9, 10], oral [8], and ovarian [21]. Reports indicated the specific role of GSK3β isoform in pancreatic [7] and non-small cell lung cancer cells [22].…”
Section: Introductionmentioning
confidence: 93%